La actividad física como elemento motivador en el contexto educativo de los estudiantes del séptimo año en la Unidad Educativa Luz del Mundo, cantón Ventanas - Elizalde Arias, Orly Moisés (2022)
This thesis deals with motivation as a motivating element in the educational context in seventh year basic students of the Luz del Mundo educational unit, helping students to practice physical activity. Various concepts such as activity, physical activity, motivation, among others, are addressed. Motivation is a factor that influences human behavior, being studied from different fields, the stages of the motivational cycle are shown, the types of reasons that guide the practice of physical exercise, the various psychological theories on motivation.